Hopf algebra actions and transfer of Frobenius and symmetric properties - Dăscălescu, S.; Năstăsescu, C.; Năstăsescu, L. (Mathematica Scandinavica, 2020)
If H is a finite-dimensional Hopf algebra acting on a finite-dimensional algebra A, we investigate the transfer of the Frobenius and symmetric properties through the algebra extensions A^HAA# H.